2015
DOI: 10.1111/acel.12311
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte maintenance during healthy aging requires no substantial alterations in cellular turnover

Abstract: In healthy humans, lymphocyte populations are maintained at a relatively constant size throughout life, reflecting a balance between lymphocyte production and loss. Given the profound immunological changes that occur during healthy aging, including a significant decline in T-cell production by the thymus, lymphocyte maintenance in the elderly is generally thought to require homeostatic alterations in lymphocyte dynamics. Surprisingly, using in vivo 2H2O labeling, we find similar dynamics of most lymphocyte sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
137
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(154 citation statements)
references
References 49 publications
(77 reference statements)
11
137
0
Order By: Relevance
“…2A). This observed increase in the T cell proliferation rate is in general agreement with empirical data showing that, in comparison with young adults, the naive T cell turnover rate in elderly humans either doubles (9) or does not change significantly in the CD4 compartment (65), and it increases by ∼3-fold in the CD8 compartment (65). An increase in T cell proliferation at old age has also been observed in rhesus macaques (7).…”
Section: Discussionsupporting
confidence: 90%
“…2A). This observed increase in the T cell proliferation rate is in general agreement with empirical data showing that, in comparison with young adults, the naive T cell turnover rate in elderly humans either doubles (9) or does not change significantly in the CD4 compartment (65), and it increases by ∼3-fold in the CD8 compartment (65). An increase in T cell proliferation at old age has also been observed in rhesus macaques (7).…”
Section: Discussionsupporting
confidence: 90%
“…As thymic export stops or diminishes, the maintaining peripheral T cell pool proliferates, replenishing the peripheral space and gradually acquiring an effector/memory phenotype, as also seen in lymphopenic conditions and aging (8,9,13,30). This slowly results in the loss of naive T cells and skewing toward the effector/memory phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…After the first year of life, naive T cell production in the thymus starts to decline, resulting in a very minimal production rate in healthy adults (3)(4)(5)(6). Even though the adult thymus is still able to produce new naive T cells (7,8), we and others have shown that, in contrast to what is seen in mice, most of the naive T cell population in humans is maintained by homeostatic proliferation (9,10). Due to increased homeostatic proliferation or decreased cell death, only a marginal decrease of the overall size of the naive T cell pool is observed during aging (11)(12)(13)(14)(15).…”
Section: Ccr7mentioning
confidence: 99%
“…Naïve CD4 + T-cells feature low levels of proliferation while maintaining their naïve phenotype, as demonstrated by studies using in vivo incorporation of deuterated water or Bromodeoxyuridine (BrdU) (7, 84, 85). It remains unclear whether naïve cell turnover changes with age (8, 77, 86, 87), as well as with the time span since thymic egress (2, 8, 76).…”
Section: Thymic Versus Peripheral Contribution For Naïve Cd4+ T-cell mentioning
confidence: 99%